2021
DOI: 10.1007/s00540-020-02886-5
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced anaphylaxis during general anesthesia in 14 tertiary hospitals in Japan: a retrospective, multicenter, observational study

Abstract: Since perioperative anaphylaxis occurs suddenly, and it can be life-threatening, anesthesiologists need to have sufficient knowledge of the epidemiology of perioperative anaphylaxis and appropriate coping strategies to deal with it. Recent studies conducted in Western countries reported the characteristics of perioperative anaphylaxis in each country. However, there are few studies of perioperative anaphylaxis in Japan. To bridge the gap between Japan and other countries, the data of 46 anaphylaxis patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Certainly, the diagnosis is not easy during induction of general anesthesia because of the multiple drugs administered at this time and the presence of other confounding factors that can lead to hypotension and hypoxia. Reexamination of the characteristics of the cases that occurred at anesthesia induction in our article showed that nine of the 13 cases were caused by rocuronium [2]. In contrast, there was only one case caused by propofol and none by opioids [2].…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Certainly, the diagnosis is not easy during induction of general anesthesia because of the multiple drugs administered at this time and the presence of other confounding factors that can lead to hypotension and hypoxia. Reexamination of the characteristics of the cases that occurred at anesthesia induction in our article showed that nine of the 13 cases were caused by rocuronium [2]. In contrast, there was only one case caused by propofol and none by opioids [2].…”
mentioning
confidence: 62%
“…Reexamination of the characteristics of the cases that occurred at anesthesia induction in our article showed that nine of the 13 cases were caused by rocuronium [2]. In contrast, there was only one case caused by propofol and none by opioids [2].…”
mentioning
confidence: 62%
“…The most common cause was rocuronium use, as corroborated by a previous report. 4 POA because of rocuronium use manifested not only as a type I allergy with specific IgE antibodies, but also through histamine release owing to the stimulation of Mas-related G protein-coupled receptor X2 in mast cells. 6 Hence, the use of this high-risk agent should be carefully considered.…”
Section: Discussionmentioning
confidence: 99%
“…Only facilities, such as university hospitals, that can dispatch samples for this test participate, which may introduce bias. 4, 5 To our knowledge, no study has included secondary health care providers that do not have an experimental laboratory setup. The Social Welfare Organization Saiseikai Imperial Gift Foundation, Inc. is a group of institutions established for the poor in 1911 by Emperor Meiji.…”
Section: Introductionmentioning
confidence: 99%
“…We read the article by Horiuchi et al [1] with interest. They have reported the data on the agents that cause anaphylaxis during general anesthesia.…”
Section: To the Editormentioning
confidence: 99%